Advances in atomic, molecular, and optical physics. - Arimondo, E.; Berman, Paul R., 1945-; Lin, Chun C. (Academic Press, 2010)
This volume continues the tradition of the Advances series. It contains contributions from experts in the field of atomic, molecular, and optical (AMO) physics. The articles contain some review material, but are intended to provide a comprehensive picture of recent important developments in AMO physics. Both theoretical and experimental articles are included in the volume. . International experts . Comprehensive articles . New developments.